2019
DOI: 10.2174/1389200220666190130161758
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Methotrexate Pharmacogenetics in Childhood Acute Lymphoblastic Leukaemia

Abstract: Background: In the past two decades, a great body of research has been published regarding the effects of genetic polymorphisms on methotrexate (MTX)-induced toxicity and efficacy. Of particular interest is the role of this compound in childhood acute lymphoblastic leukaemia (ALL), where it is a pivotal drug in the different treatment protocols, both at low and high doses. MTX acts on a variety of target enzymes in the folates cycle, as well as being transported out and into of the cell by several transmembran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 165 publications
1
17
0
3
Order By: Relevance
“…High-dose methotrexate (HDMTX) is commonly defined as an intravenous dose greater than 500 mg/m 2 (Howard et al, 2016), and HDMTX is recommended as an essential component of chemotherapy for ALL and non-Hodgkin lymphoma (NHL) in clinical guidelines (National Comprehensive Cancer Network, 2021a;. Although breakthroughs have been made in the complex treatment of hematological malignancies, HDMTX still plays a key role and is established as the first-line drug (Gervasini and Mota-Zamorano, 2019). However, patients differ largely in their response to treatment regarding HDMTX pharmacokinetics and toxicities, even when given the identical dose (Schmiegelow, 2009;Giletti and Esperon, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…High-dose methotrexate (HDMTX) is commonly defined as an intravenous dose greater than 500 mg/m 2 (Howard et al, 2016), and HDMTX is recommended as an essential component of chemotherapy for ALL and non-Hodgkin lymphoma (NHL) in clinical guidelines (National Comprehensive Cancer Network, 2021a;. Although breakthroughs have been made in the complex treatment of hematological malignancies, HDMTX still plays a key role and is established as the first-line drug (Gervasini and Mota-Zamorano, 2019). However, patients differ largely in their response to treatment regarding HDMTX pharmacokinetics and toxicities, even when given the identical dose (Schmiegelow, 2009;Giletti and Esperon, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that the increase of dihydrofolate reductase and the damage of MTX transport are key factors in MTX resistance in childhood ALL (41). Previous studies have measured the difference in MTX resistance-related mRNA expression levels in childhood leukaemia by standardized RT-qPCR based on a competitive template, and observed that in T-ALL, compared with ordinary/pre-B-ALL, the difference in MTX resistance, dihydrofolate reductase (DHFR), thymidylate synthetase (TS) and folylpolyglutamate synthase mRNA expression levels are increased (22,42,43). The present results suggested that HSH2D is one of the important factors affecting MTX resistance, and identified via gene manipulation that HSH2D expression is necessary for HuT-78 cells resistance to MTX.…”
Section: Discussionmentioning
confidence: 99%
“…Современные исследования позволили сделать вывод о том, что одной из важнейших причин индивидуальных различий в фармакологическом ответе на лечение МТХ являются генетические особенности пациентов, определяющие до 50 % всех атипичных реакций. Согласно полученным данным, среди факторов, влияющих на терапевтический эффект и безопасность МТХ, большая роль отводится однонуклеотидным полиморфизмам в генах, определяющим индивидуальные особенности ФК МТХ [14][15][16].…”
Section: метотрексатunclassified
“…Наличие SNP rs639174 в гене DROSHA связано с гастроинтестинальной токсичностью, индуцированной МТХ у детей с B-линейным ОЛЛ. Это исследование впервые продемонстрировало потенциальную роль полиморфизмов в генах процессинга miRNA для прогнозирования токсичности при лечении ОЛЛ [16,20]. Дальнейшие исследования miRNA, эпигенетики и полногеномного секвенирования смогут прояснить индивидуальную вариабельность эффективности и токсичности МТХ.…”
Section: метотрексатunclassified
See 1 more Smart Citation